Revision total hip arthroplasty is associated with significantly higher opioid consumption as compared to primary total hip arthroplasty in the acute postoperative period. (September 2020) - Bernstein, Jenna A; Feng, James; Mahure, Siddharth A; Schwarzkopf, Ran; Long, William J
Background: There are currently a lack of investigations that characterised narcotic utilisation following revision total hip arthroplasty (THA). We sought to determine if immediate post-surgical opioid use was different between revision THA and primary THA. Methods: A single institution total joint arthroplasty database was used to identify adult patients who underwent revision THA or primary THA from 2016 to 2019. Morphine milligram equivalents (MME) were calculated for different time periods. Results: 6977 patients were identified, 89.72% primary THA and 10.28% revision THA. Aggregate opioid consumption was higher for revision THA patients (317.40 MME vs. 93.01 MME), as was opioid consumption in the first 24 hour and second 24-hour periods. Visual analogue pain (VAS) scores were significantly higher in the 0–12 hour postoperative and the 12–24 hours postoperative periods in the revision THA group. Conclusions: Patients undergoing revision THA had significantly higher narcotic utilisation than those undergoing primary THA, particularly in the first 24 hours postoperatively.